(untitled) (TAJ: Journal of Teachers Association, 2019)
Posterior urethral valves (PUV) constitute the most common infra-vesical urinary obstruction in boys. PUV are often accompanied by severe consequences to the lower and upper urinary tract (LUT, UUT). They also represent a major urological cause for pediatric renal transplantations. Surgical options for primary management invariably aim at abolition of valves. However, temporary urinary diversion may sometimes be a viable alternative, especially in critically ill patients or preterm infants. It was a retrospective, descriptive study which was conducted at the Department of Pediatric Surgery, Rajshahi Medical College from January 2018 to December 2018. All stable patients with the diagnosis of posterior urethral valves were included in the study. Endoscopic valve fulguration was performed in all diagnosed patients using bugbee electrode and an adequate sized cystoscope. The procedure was performed under general anesthesia and the urinary bladder was drained with a suitable size Foley’s or silicon catheter for 14days. Patients were discharged from the hospital 48-72 hours after the procedure on oral antibiotics and were advised to come to the outpatient department for follow up visits for a period of 6 months. A total of 84 patients were included in the study. All were males with a mean age of 6.5years ranging from 6 months to 12 years. Sixty five patients were without any diversion while 19 had vesicostomy or ureterostomy already done in our department or somewhere else. Stricture urethra was seen in 5 patients, incontinence of urine was seen in 7 patients, nocturnal enuresis in 15 patients and recurrent urinary tract infection in 19 patients. Chronic renal failure was seen in 4 patients while 16 patients lost the follow up.18 patients had an uneventful recovery. Urethral valve ablation is the definitive treatment of posterior urethral valves. Endoscopic urethral valve fulguration is safe, effective and definitive way of management for posterior urethral valves. Early treatment improves the quality of life and prevents the ongoing renal damage. Early presentation in fetal and neonatal life has worst prognosis due to associated renal dysplasia. TAJ 2018; 31(2): 68-72